2019
DOI: 10.4269/ajtmh.18-0678
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Burkholderia pseudomallei in the Environment of Farms in Thanlyin and Hmawbi Townships, Myanmar

Abstract: . Melioidosis is a tropical infection, first described in Myanmar but now rarely diagnosed there, which is widespread in Southeast Asia. The infection is predominantly acquired by people and animals through contact with soil or water. This study aimed to detect the causative organism, Burkholderia pseudomallei , in environmental samples from farms in Thanlyin and Hmawbi townships near Yangon, Myanmar. One hundred and twenty soil samples and 12 water samples were collected and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Limmathurotsakul et al suggested that the burden of melioidosis in Myanmar was more than 6,000 cases and 3,000 deaths per year. [1] Recently two small studies confirmed the presence of B. pseudomallei in the soil in three regions (Yangon, Ayeyarwaddy and Bago) [26,27] but the national distribution in Myanmar remains unknown. We therefore carried out a nationwide study to identify the geographical distribution of B. pseudomallei in soil in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limmathurotsakul et al suggested that the burden of melioidosis in Myanmar was more than 6,000 cases and 3,000 deaths per year. [1] Recently two small studies confirmed the presence of B. pseudomallei in the soil in three regions (Yangon, Ayeyarwaddy and Bago) [26,27] but the national distribution in Myanmar remains unknown. We therefore carried out a nationwide study to identify the geographical distribution of B. pseudomallei in soil in Myanmar.…”
Section: Introductionmentioning
confidence: 99%
“…Recently two small studies confirmed the presence of B . pseudomallei in the soil in three regions (Yangon, Ayeyarwaddy and Bago) [ 26 , 27 ] but the national distribution in Myanmar remains unknown. We therefore carried out a nationwide study to identify the geographical distribution of B .…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of culture-confirmed human melioidosis cases at Yangon General Hospital in 2009 prompted soil sampling on two farms in nearby townships, Hmawbi and Thanlyin. B. pseudomallei was isolated from seven soil samples: five from Hmawbi and two from Thanlyin 11 . Subsequently a systematic survey of the environment in Myanmar was initiated in 2018 in order to identify areas of high melioidosis risk (Smithuis, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“… 6 Human immunodeficiency virus (HIV) infection does not appear to increase the risk of melioidosis. 7 Recent soil sampling surveys have demonstrated the presence of B. pseudomallei in central Myanmar, including Yangon, 8 , 9 yet there have been few published clinical cases in Myanmar since 1942. 10 , 11 Difficulties diagnosing B. pseudomallei in resource-poor endemic regions include lack of physician awareness of the disease, clinical and radiological mimicry of other bacterial infections, especially tuberculosis (TB), 12 and limited access to specialist laboratory facilities and expertise required for diagnosis.…”
Section: Introductionmentioning
confidence: 99%